Sublethal effects of imidacloprid on the whitefly parasitoid Encarsia formosa Gahan - Drobnjaković, Tanja; Marčić, Dejan; Prijović, Mirjana; Perić, Pantelija; Milenković, Slobodan; Bošković, Jelena (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
Acute toxicity of an imidacloprid-based product (Confidor 200 SL) to pupae of the whitefly parasitoid Encarsia formosa Gahan (Hymenoptera: Aphelinidae), and its effects on life history traits and population growth in F1 generation of the surviving parasitoid females of a commercial strain (“Dutch” strain, D) and two local populations from Serbia (Bujanovac, B; Negotin, N) were examined in laboratory bioassays. All trials were carried out at 27±1°C temperature and 60±10% relative humidity, and under 16/8 h daylight/darkness photoperiod in four replications. In acute toxicity bioassays, tobacco leaves carrying parasitoid pupae were treated with a series of symmetrical concentrations (800, 400, 200, 100, 50 and 25 mg a.i./l) covering a 10-90% mortality range. The product based on imidacloprid, applied directly onto parasitoid pupae at mean lethal concentrations (LC50) determined in the acute toxicity assays (30 mg/l, 20 mg/l and 25 mg/l, for populations B, N and D, respectively), significantly affected the survival of females developed from the treated pupae, extended the duration of juvenile development (by 1.81, 1.59 and 1.73 days for populations B, N and D, respectively), significantly reduced total parasitism of females D (25.92 %), total female adult emergence in populations B (27.48 %) and D (17.92 %), and significantly reduced the instantaneous rate of increased only of females N (4.23 %). Considering the high acute toxicity of the imidacloprid product to the pupal stage of E. formosa, and significant reductions in life table and population parameters, imidacloprid is not considered compatible for simultaneous use with the parasitoid E. formosa. A more precise assessment of risks involved in the use of that insecticide requires a more detailed testing in the field. The implications of these results for the concept of integrated control of the greenhouse whitefly are discussed.